Dependent failure behavior modeling for risk and reliability: A systematic and critical literature review - Zeng, Zhiguo; Barros, Anne; Coit, David (Reliability engineering & system safety, 2023)
This paper presents a systematic and critical literature review on dependent failure behavior modeling in risk and reliability. A literature search is conducted systematically based on pre-defined protocols. The resulting papers are first analyzed through a meta-data and bibliometric analysis, in which the trend of publication growth, important publication sources and authors, collaboration among the authors are identified. The evolution of research topics in three time periods (prior to mid-1990s, mid-1990s - 2010 and 2010 - present) is also discussed through a semantic clustering. Then, the most important papers from the literature search are chosen for a content analysis and critical review. The main results of the critical literature review include: First, we summarize the dependent failure behavior in different system hierarchies, i.e., failure mechanism level, component level, system level and systems-of-systems level. In each level, the main dependent failure behavior from literature is discussed with examples. Second, we develop a classification framework for the dependent failure behavior models. The most frequently-used models in each category are critically reviewed, based on which we identify five challenging problems the current dependency models face, give our perspectives on their possible solutions, and discuss future research opportunities. •Dependent failure behavior modeling is reviewed.•Typical dependent failure behavior in different system hierarchies is summarized.•A classification framework is presented frequently-used dependent failure models.•Challenges to current and opportunities for future research are presented.